Pore-Water Geochemical Gradients of Sulfate, Calcium, Magnesium, and Iodide Correlated With Underlying Gas Hydrate Potential: A Case Study of the Shenhu Area, South China Sea - Ai, Xinyu; Zha, Rihuan; Lai, Yijun; Yang, Tao; Su, Pibo (Frontiers in Earth Science, 2022)
Geochemical profiles in pore water of marine sediments have been considered as important indicators of gas hydrate occurrence. In the gas hydrate area around the world, the decrease of sulfate, calcium, and magnesium concentrations with depth mainly results directly or indirectly from the anaerobic oxidation of methane (AOM). The ubiquitous abnormally high concentration gradients of iodide in the research area reflect the large methane-generating potential of the area. Thus, we explore the feasibility of using gradients of sulfate, iodide, and authigenic carbonate precipitation as indicators for gas hydrate in the regional exploration of gas hydrate formation. We test the criterion in the gas hydrate zone in the South China Sea (SCS) for the recognition of gas hydrate by using the gradients of sulfate, calcium plus magnesium, and iodide. Contour maps of pore-water gradients from expeditions in the study area are used to correlate the key gradients to underlying gas hydrate occurrence. The results show that the largest potential gas hydrate indicated by the contour maps of the indicators are well consistent with the discovery of GMGS1 and GMGS3 expedition. It implies the possible applicability of this geochemical method in gas hydrate exploration. Also, we identify a promising area in the South China Sea for future gas hydrate investigations. It is the first collective application of the gradients of sulfate, calcium plus magnesium, and iodide to a gas hydrate terrane, especially to a large area of the SCS. We believe that the result of this research will benefit the future exploration of gas hydrate and will arouse a lot of interest from other researchers.